2011
DOI: 10.5539/ijms.v3n4p117
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Verification of the Accuracy of Valuation Estimates Emanating From Nigerian Valuers: A Case Study of Lagos Metropolis

Abstract: There have been increasing criticisms of the ability of Nigerian valuers to undertake investment valuations in a reliable and accurate manner. This study sought to examine with a view to validating or dispensing the criticisms as to whether Nigerian valuers are capable of undertaking investment valuations in a reliable and accurate manner or not. To achieve this aim, the paper employed quasi-experimental survey methods. Forty five (45) estate surveying and valuation firms were sampled in Lagos Metropolis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
(14 reference statements)
2
10
0
Order By: Relevance
“…The study established that there was a statistically significant difference between valuations and subsequent transaction prices signifying low valuation accuracy. Several studies including Ayedun et al (2011), Ogunba andAjayi (1998), andOgunba andAjayi (2007) reported similar findings. Furthermore, a perceptual study by Adegoke et al (2013) noted that valuers themselves do not think their valuations are accurate and reliable.…”
Section: Review Of the Relevant Literaturesupporting
confidence: 53%
“…The study established that there was a statistically significant difference between valuations and subsequent transaction prices signifying low valuation accuracy. Several studies including Ayedun et al (2011), Ogunba andAjayi (1998), andOgunba andAjayi (2007) reported similar findings. Furthermore, a perceptual study by Adegoke et al (2013) noted that valuers themselves do not think their valuations are accurate and reliable.…”
Section: Review Of the Relevant Literaturesupporting
confidence: 53%
“…Due to the fact that the property market is absolutely local in nature, the practical implications of this study cannot be generalised to other property markets outside Southwestern Nigeria. Ayedun et al (2010) sought to ascertain if valuations conducted by valuers were done in an authentic and uniform manner. The study utilised data from 131 Federal Government privatised properties that were valued by estate surveyors and valuers before their eventual sale.…”
Section: Market Value Residential Valuation Approach and Accuracymentioning
confidence: 99%
“…In addition, clients influence valuation accuracy in so many ways amongst which are "shopping for valuer" that will apportion the desired value to the appraisal, threatening to withhold payment of fees and closing the door on future patronage (Amidu and Aluko, 2007). Several related studies (Effiong and Mendie, 2019;Ayedun et al, 2010;Udoekanem, 2018) have established the existence of client pressure in the Nigerian valuation industry and how it corrodes the objectivity of valuers as they upwardly adjust values to suit their clients. Besides, a critical review of the studies carried out locally showed that they focussed more on the property markets in Southern Nigeria (Ogunba and Ajayi, 1998;Ogunba, 2004;Ajibola, 2010;Babawale and Ajayi, 2011;Oduyemi et al, 2016;Abidoye and Chan, 2018) in terms of geographical scope and none tested the ability of valuation to predict transaction price in the residential property market apart from Ogunba (2004) and Abidoye and Chan (2018)…”
Section: Review Of the Causes Of Valuation Inaccuracymentioning
confidence: 99%
See 1 more Smart Citation
“…A valuation-surveyor provides a value estimate which is a close approximation of the market-price (French & Gabrielli, 2004;Mwasumbi, 2014). However, various researchers have indicated the existence of significant differences between price and the valuation opinions over the same property by different valuers (Parker, 1998;Crosby, 2000;Ayedun, et al, 2011), an observation which raises questions on the reliability of valuation output. In Tanzania, Geho (2004) noted an average of up to 35% deviation between assessed value and realizable market-price of properties located in areas with less vibrant real estate markets.…”
Section: Introductionmentioning
confidence: 99%